Assessment of acoustic and pulsation characteristics of centrifugal pumps - Zharkovskiy Aleksandr (E3S Web of Conferences, 2019)
Numerical investigations of unsteady viscous flow in centrifugal pumps were conducted in this paper. Verification of numerical approach was done. Hydraulic components of the pump were modernized with the purpose to improve their acoustic characteristics. Modernization was held on the base of isotropic turbulence noise measuring techniques. Results were confirmed by experiment. Pressure pulsations were studied in a flow between rotating impeller and stator for initial and improved flowing parts. As a result of numerical research, various impellers with different blade outlet angles were designed. During optimization, the optimal blade outlet angle was found, which provides increased vibroacoustic characteristics while maintaining a high level of efficiency.